PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Laresia, Rizka Syahi; Edriati, Sofia; Handayani, Siskha (Jurnal Pelangi : Research of Education and Development, 2020)
The aim of this research to know that Think Pair Share type cooperative learning model influence to students understand about mathematical concepts. This research is Pre-Experimental Design with investigaton planning Pre-Test and Post-Test Group. The subjek of research are students of SMPN 2 Pariaman grade VIII.1. Research instrumen is essay test. The data analysis using t-test. Based on the results of data analysis can be concluded that there is an influence of using Think Pair Share to the understanding of mathematical concepts of class VIII.1 junior high school students